2004
DOI: 10.1093/humrep/deh388
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormality rate in human pre-embryos derived from in vitro fertilization cycles cultured in the presence of Follicular-Fluid Meiosis Activating Sterol (FF-MAS)

Abstract: BACKGROUND: The objective of the study was to investigate the effect of Follicular-fluid meiosis activating sterol (FF-MAS) when added to the culture media on the incidence of chromosomal abnormalities and pre-embryo development in human pre-embryos. METHODS: 243 women undergoing IVF/ICSI treatment donated 353 oocytes in a multicentre, prospective, randomized, double blind, four-arm, controlled trial performed at Danish and Swedish public and private IVF centers. Metaphase II oocytes were randomly assigned to:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…It should be stressed that if immature oocytes are found in normal IVFs or ICSIs 36 hours after the use of hCG, it means that they have not reacted normally to the hCG trigger, and are perhaps not normally developed. Previous research on immature oocytes collected during IVF and ICSI treatment, and subjected to IVM, showed that developmental competence is lower than in their sibling in vivo-matured oocytes, with a corresponding increased rate of aneuploidy in the blastomeres of the generated embryos (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stressed that if immature oocytes are found in normal IVFs or ICSIs 36 hours after the use of hCG, it means that they have not reacted normally to the hCG trigger, and are perhaps not normally developed. Previous research on immature oocytes collected during IVF and ICSI treatment, and subjected to IVM, showed that developmental competence is lower than in their sibling in vivo-matured oocytes, with a corresponding increased rate of aneuploidy in the blastomeres of the generated embryos (6,7).…”
mentioning
confidence: 99%
“…Reports suggest that this new technique remains challenging, and that in many areas, the standard operating procedures still need to be optimized (9). Among the many unresolved issues are: [1] the necessity to pretreat patients with gonadotropins, [2] the target range of follicle diameters to aspirate, [3] the aspiration pressure for oocyte collection, [4] the maturation medium composition, [5] the optimal time for maturation, [6] the time for insemination or sperm injection, and [7] the steroid substitution regimen to prepare a receptive endometrium in the transfer cycle.…”
mentioning
confidence: 99%
“…Our study showed that LH induced CYP51 expression in follicular cells but might not contribute to oocytes maturation; instead, a delayed expression may be related to the cases that MAS improves oocyte cytoplasmic maturation [mouse ( 53,54 ), calf ( 20 ), human ( 55 )] and protects oo-…”
Section: Discussionmentioning
confidence: 69%
“…The results showed that both FSH and LH upregulated CYP51 expression cytes from precocious chromatins segregation [mouse ( 56 ); and human ( 55,57 )]. Also, CYP51-mediated MAS production is involved in primary follicle formation in fetal ovary and in sperm meiosis in testis ( 8,13,58 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this study, FF-MAS was only available in an ethanol-based solution. This had been used in other studies with denuded human oocytes [17][18], without any demonstrated negative effect on embryo development or chromosomal status. In the study by Cavilla et al [17] increased maturation and fertilisation rates of denuded human GV oocytes was shown after supplementation with FF-MAS ( in an 0.5% ethanol formulation) to the culture medium.…”
Section: Discussionmentioning
confidence: 99%